2017
DOI: 10.1016/j.scitotenv.2016.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to major roadways and prospectively-measured time-to-pregnancy and infertility

Abstract: We aimed to study the potential impact of proximity to major roadways on time-to-pregnancy and infertility in couples attempting pregnancy in the Longitudinal Investigation of Fertility and Environment (LIFE) study (2005-2009), a population-based, prospective cohort study. Couples attempting pregnancy (n=500) were enrolled and followed prospectively until pregnancy or 12 months of trying and 393 couples (78%) had complete data and full follow-up. Time-to-pregnancy was based on a standard protocol using fertili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…As the number of couples seeking medical treatment for infertility continues to rise (Kushnir et al 2017), a better understanding of how environmental factors impact outcomes of IVF remains an important health issue particularly given the high costs and psychological toll of having to undergo multiple IVF treatments (Brandes et al 2009; Katz et al 2011). Our research not only corroborates evidence from studies among women attempting to conceive naturally (Mahalingaiah et al 2016; Mendola et al 2017) and through assisted reproduction (Legro et al 2010), it further highlights that exposure to traffic-related air pollution may have an effect on early implantation failure. More research is needed to evaluate which specific traffic-related air pollutant(s) may be responsible for this association and whether there is a specific window of heightened susceptibility to its adverse effects.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…As the number of couples seeking medical treatment for infertility continues to rise (Kushnir et al 2017), a better understanding of how environmental factors impact outcomes of IVF remains an important health issue particularly given the high costs and psychological toll of having to undergo multiple IVF treatments (Brandes et al 2009; Katz et al 2011). Our research not only corroborates evidence from studies among women attempting to conceive naturally (Mahalingaiah et al 2016; Mendola et al 2017) and through assisted reproduction (Legro et al 2010), it further highlights that exposure to traffic-related air pollution may have an effect on early implantation failure. More research is needed to evaluate which specific traffic-related air pollutant(s) may be responsible for this association and whether there is a specific window of heightened susceptibility to its adverse effects.…”
Section: Discussionsupporting
confidence: 84%
“…Among women in the Nurses’ Health Study II, those who lived within 200 m of a major roadway had 1.11 (95% CI 1.02–1.20) times the risk of self-reported infertility compared to women living ≥200 m away (Mahalingaiah et al 2016). Among couples in the Longitudinal Investigation of Fertility and the Environment (LIFE) Study, the likelihood of pregnancy was increased 3% for every 200 m further away the couples’ residence was from a major roadway (Mendola et al 2017). Regarding specific air pollutants and spontaneous fertility, a cross-sectional study found that the number of live births per 1000 women between the ages of 15 and 44 years was significantly lower in census tracts with higher exposure to NO x , nitrogen dioxide (NO 2 ), fine particular matter (PM 2.5 ), and course particulate matter (PM 10 ) (Nieuwenhuijsen et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among women attempting to conceive without medical assistance, those residing closer to major roadways were shown to have a higher risk of infertility (Mahalingaiah et al. 2016) and longer time to pregnancy (Mendola et al. 2017), and those with higher exposure to NO2, PM2.5, and PM10 had lower census tract–level fertility rates (Nieuwenhuijsen et al.…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported data indicated that ovulatory disorder and male infertility may have driven these associations [ 11 ]. In Texas and Michigan, among 393 couples attempting to conceive, couples were 3% more likely to become pregnant for each additional 200 m they lived away from a major roadway [ 12 ]. These changes in fertility may result from endocrine disruption, oxidative stress, or DNA modifications caused by pollutants [ 10 ].…”
Section: Discussionmentioning
confidence: 99%